О некоторых аспектах применения метаэвристических стратегий оптимизации - Пепеляев, В.А. (Теорія оптимальних рішень, 2005)
The features of application based on concepts simulation-omtimization integration and metaheuristic strategy of optimization of the approach to development of the imitating appendices focused on search of optimal design decisions for systems research.